Side effects may include: Consequence neglect in generating solutions - Christopher Rodriguez; Daniel M. Oppenheimer (PLoS ONE, 2025)
Strategies designed to address specific problems often give rise to unintended, negative consequences that, while foreseeable, are overlooked during strategy formulation and evaluation. We propose that this oversight is not due to a lack of knowledge but rather a cognitive bias rooted in focalism—the tendency to focus narrowly on the primary objective, ignoring other relevant factors, such as potential consequences. We introduce the concept of consequence neglect, where problem solvers fail to generate or consider downstream effects of their solutions because these consequences are not central to the proximal goal. Across four studies, we provide evidence supporting this phenomenon. Specifically, we find that individuals rate strategies more negatively after being prompted to generate both positive and negative consequences, suggesting that negative outcomes are not naturally weighted unless attention is explicitly drawn to them. We conclude by discussing the broader implications of consequence neglect for policymaking, business, and more general problem solving, and offer directions for future research.